2019
DOI: 10.18632/aging.102013
|View full text |Cite
|
Sign up to set email alerts
|

Nectandrin B-mediated activation of the AMPK pathway prevents cellular senescence in human diploid fibroblasts by reducing intracellular ROS levels

Abstract: Nectandrin B (NecB) is a bioactive lignan compound isolated from Myristica fragrans (nutmeg), which functions as an activator of AMP-activated protein kinase (AMPK). Because we recently found that treatment with NecB increased the cell viability of old human diploid fibroblasts (HDFs), the underlying molecular mechanism was investigated. NecB treatment in old HDFs reduced the activity staining of senescence-associated β-galactosidase and the levels of senescence markers, such as the Ser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 66 publications
1
18
1
Order By: Relevance
“…The main chemical components in the three different N. lappaceum extracts were identified by comparing the references with the MS fragmentation pattern of each peak (Figure S44 in Supplementary Material). Specifically, the DAD chromatogram and the MS/MS fragmentation profiles showed that the pulp of N. lappaceum mainly contained disaccharides, while the major components of the N. lappaceum peels were identified as gallic acid, corilagin, and geraniin, which was consistent with previous reports [9]. The extract of the N. lappaceum seed was found to be dominated by flavonoids based on molecular networking.…”
Section: Molecular Networking Of the Seed Pulp And Peel Extracts Of N Lappaceum Fruitssupporting
confidence: 89%
See 1 more Smart Citation
“…The main chemical components in the three different N. lappaceum extracts were identified by comparing the references with the MS fragmentation pattern of each peak (Figure S44 in Supplementary Material). Specifically, the DAD chromatogram and the MS/MS fragmentation profiles showed that the pulp of N. lappaceum mainly contained disaccharides, while the major components of the N. lappaceum peels were identified as gallic acid, corilagin, and geraniin, which was consistent with previous reports [9]. The extract of the N. lappaceum seed was found to be dominated by flavonoids based on molecular networking.…”
Section: Molecular Networking Of the Seed Pulp And Peel Extracts Of N Lappaceum Fruitssupporting
confidence: 89%
“…Recent data have demonstrated that the activation or enforced expression of sirtuins (SIRTs) increases lifespan in animal models, making sirtuins a potential target for healthy aging. Silent mating type information regulation 2 homolog (SIRT1), also known as NAD-dependent deacetylase-1, also mediates the beneficial antiaging effects of caloric restriction and natural products, such as resveratrol, which can extend the human lifespan [9].…”
Section: Introductionmentioning
confidence: 99%
“…Jang et al. (2019) showed that nectandrin B‐mediated activation of the AMPK pathway prevents cellular senescence by reducing intracellular ROS levels. In terms of sperm, AMPK is an important connection between metabolism energy and sperm fertility, which helps to regulate sperm motility, mitochondrial activity, membranes and acrosome reaction (Martin‐Hidalgo et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factor expression analysis was performed as described previously. 30 MIA PaCa-2 and BxPC-3 cells were seeded on a black 96-well plate and grown for 24 hours. The cells were transduced using the lentiviral supernatant for 24 hours.…”
Section: Methodsmentioning
confidence: 99%